2013
DOI: 10.7547/1030508
|View full text |Cite
|
Sign up to set email alerts
|

Does Footwear Affect Balance?

Abstract: Background: Despite falls being a major concern for people living with somatosensory deficit, little is known about the perceived impact of footwear and footwear features on balance. Clinical relevance is increased given that therapeutic footwear is often provided to people with diabetes to reduce foot ulcer risk. This qualitative study aims to explore the experiences and views of people with diabetes and neuropathy who have recently fallen to understand whether footwear type is perceived to affect balance or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It has been shown that foot and ankle exercise programmes have influenced balance and ankle movement [48], and older people are more likely to keep to an exercise programme when they are supervised [49]. Similarly, footwear choices have been a contributing factor in falls and influence a person’s balance, walking confidence, and day-to-day activities [6]. The participants in this study did not usually wear shoes inside the home, as they felt that they were more likely to stumble when wearing shoes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that foot and ankle exercise programmes have influenced balance and ankle movement [48], and older people are more likely to keep to an exercise programme when they are supervised [49]. Similarly, footwear choices have been a contributing factor in falls and influence a person’s balance, walking confidence, and day-to-day activities [6]. The participants in this study did not usually wear shoes inside the home, as they felt that they were more likely to stumble when wearing shoes.…”
Section: Discussionmentioning
confidence: 99%
“…Hosiery can contribute to shock absorbency [4], and foot exercises promote balance and ankle flexibility [5]. Shoes provide balance and security when walking [6]. Foot problems, especially pain, can have a detrimental effect on quality of life [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…A dynamic measure was selected as an outcome for this study to reflect the fact that the majority of falls occur while people undertake dynamic activities. More specifically step reaction time was considered of particular relevance to our target patient group because people with diabetes and neuropathy interviewed for our previous work described catching a toe whilst stepping up a change in level as a common event behind their fall [ 16 ]. In addition, others have used a ‘timed stepping test’ to prospectively classify the falls status of elderly community dwellers [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…When people are asked about their therapeutic shoes, common complaints and reasons for not wearing them are that the shoes are found to be unattractive, too big, uncomfortable, or difficult to walk in. 1 , 14 – 16 These reasons are well known to clinicians prescribing therapeutic shoes, but there might be other, less obvious, factors that influence an individual’s decision to wear or not wear therapeutic shoes. These factors might include perceived severity of the foot condition, sensory neuropathy, and beliefs about what causes foot ulcers.…”
Section: Introductionmentioning
confidence: 99%